2020
DOI: 10.1159/000503636
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of VEGF in the Cross Talk between Pterygium and Dry Eye and Its Clinical Significance

Abstract: Purpose: To examine whether dry eye severity is a risk factor for pterygium activity and whether vascular endothelial growth factor (VEGF) is crucial in the cross talk between pterygium and dry eye. Methods: A total of 103 patients with primary pterygium (Pteg) were included in the study group; they were divided into 2 groups according to the complication of dry eye (DE) (Pteg + DE group, Pteg -DE group). Further, 60 patients with just dry eye (DE group) and 60 normal individuals (normal) were included as 2 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…1,2 It comprises a wing-shaped progressively growing fibrovascular tissue usually located on the nasal side, and could lead to visual impairment, astigmatism, and dry eye. 3 Over the years, various medical measures, such as anti-inflammatory eye drops and chemotherapeutic agents have been used in the treatment of pterygium. Surgical removal can be performed if the patient desires symptomatic or cosmetic improvement, but recurrence remains the main complication.…”
mentioning
confidence: 99%
“…1,2 It comprises a wing-shaped progressively growing fibrovascular tissue usually located on the nasal side, and could lead to visual impairment, astigmatism, and dry eye. 3 Over the years, various medical measures, such as anti-inflammatory eye drops and chemotherapeutic agents have been used in the treatment of pterygium. Surgical removal can be performed if the patient desires symptomatic or cosmetic improvement, but recurrence remains the main complication.…”
mentioning
confidence: 99%
“…Moreover, VEGF concentrations did not significantly differ between the primary and recurrent groups. Many studies have reported that VEGF is involved in causing pterygia 13 , 17 , 30 . However, few studies have compared VEGF concentrations between primary and recurrent pterygium groups 30 .…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms could expand the inflammatory reactions in pterygium tissue and the ocular surface 33 . Liu et al described that VEGF and MMP-9, which are upregulated by VEGF through the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) signaling pathway, play important roles in the crosstalk between pterygia and DE 15 , 17 , 33 . In this study, we also found significantly higher VEGF levels in the pterygium group, which were 1.97, 3.41, and 5.20 times those of the HC group regardless of DE status, in pterygium patients with DE compared with HCs with DE and in pterygium patients with DE compared with pterygium patients without DE, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations